Demonstrating kHz Frequency Actuation for Conducting Polymer Microactuators. (12th May 2014) - Maziz, Ali; Plesse, Cedric; Soyer, Caroline; Chevrot, Claude; Teyssié, Dominique; Cattan, Eric; Vidal, Frederic
<x xml:space="preserve">Abstract</x> This paper reports results on ionic EAP micromuscles converting electrical into micromechanical response in open‐air. Translation of small ion motion into large deformation in bending microactuator and its amplification by fundamental resonant frequency are used as tools to demonstrate that small ion vibrations can still occur at frequency as high as 1000 Hz in electrochemical devices. These results are achieved through the microfabrication of ultrathin conducting polymer microactuators. First, the synthesis of robust interpenetrating polymer networks (IPNs) is combined with a spincoating technique in order to tune and drastically reduce the thickness of conducting IPN microactuators using a so‐called "trilayer" configuration. Patterning of electroactive materials as thin as 6 μm is demonstrated with existing technologies, such as standard photolithography and dry etching. Electrochemomechanical characterizations of the micrometer sized beams are presented and compared to existing model. Moreover, thanks to downscaling, large displacements under low voltage stimulation (±4 V) are reported at a frequency as high as 930 Hz corresponding to the fundamental eigenfrequency of the microbeam. Finally, conducting IPN microactuators are then presenting unprecedented combination of softness, low driving voltage, large displacement, and fast response speed, which are the keys for further development to develop new MEMS.